2021
DOI: 10.1007/s11274-021-03197-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of poly (vinyl alcohol) by an orychophragmus rhizosphere-associated fungus Penicillium brevicompactum OVR-5, and its proposed PVA biodegradation pathway

Abstract: In recent years, the utilisation of endophytes has emerged as a promising biological treatment technology for the degradation of plastic wastes such as biodegradation of synthetic plastics. This study, therefore, aimed to explore and extensively screen endophytic fungi (from selected plants) for efficient in vitro polyvinyl alcohol (PVA) biodegradation. In total, 76 endophytic fungi were isolated and cultivated on a PVA screening agar medium. Among these fungi, 10 isolates showed potential and were subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Penicillium brevicompactum C2559 was isolated from a nine-week-immersed PLA sample, which corresponds to a PLA sample that also had an ASV associated with the genus Penicillium in our metabarcoding data, and cultured using on a PS-supplemented medium. A previous study has demonstrated the ability of this species to degrade polyvinyl alcohol (PVA) [ 70 ], a polymer considered as biodegradable [ 71 , 72 ], which appears consistent with our results demonstrating a potential for another biodegradable polymer, here PCL [ 73 ]. Such capabilities may be explained by their shared properties.…”
Section: Discussionsupporting
confidence: 92%
“…Penicillium brevicompactum C2559 was isolated from a nine-week-immersed PLA sample, which corresponds to a PLA sample that also had an ASV associated with the genus Penicillium in our metabarcoding data, and cultured using on a PS-supplemented medium. A previous study has demonstrated the ability of this species to degrade polyvinyl alcohol (PVA) [ 70 ], a polymer considered as biodegradable [ 71 , 72 ], which appears consistent with our results demonstrating a potential for another biodegradable polymer, here PCL [ 73 ]. Such capabilities may be explained by their shared properties.…”
Section: Discussionsupporting
confidence: 92%
“…To effectively biodegrade polyvinyl alcohol (PVA) in vitro, researchers set out to discover and broadly screen endophytic fungi (from specified plants) [42]. Seventy-six endophytic fungi were cultured in total on a PVA screening agar medium.…”
Section: Bioremediation By Penicillium Spmentioning
confidence: 99%
“…Together with the bacterial consortia, abiotic factors facilitate the mineralization, assimilation, depolymerization, and fragmentation of environmental plastic wastes into carbon dioxide, nitrogen, methane, and water molecules, monomers, dimers, and oligomers [36][37][38]. Since the 1970s, certain strains of bacteria from the genera Aspergillus [39][40][41], Penicillium [42][43][44], Streptomyces [45][46][47], Pseudomonas [48][49][50], and Bacillus [51][52][53] have been utilized to break down plastic trash. Though the microorganisms responsible for plastic breakdown have been narrowed down, further study is required to confirm the identities of the specific causes.…”
mentioning
confidence: 99%
“…These routes include scission of the polymer chain by an extracellular oxidase (dehydrogenase), followed by aldolase and hydrolase reactions, releasing compounds such as acetic acid and hydroxyl fatty acids that can be incorporated into the β-oxidation and TCA cycle, respectively [ 114 ]. Figure 26 presents a tentative metabolization route for PVOH [ 447 ].…”
Section: Polymers Susceptible To Biodegradationmentioning
confidence: 99%